2008
DOI: 10.1098/rspa.2008.0011
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness of fast travelling fronts in reaction–diffusion equations with delay

Abstract: We consider positive travelling fronts, u ( t ,  x )= ϕ ( ν . x + ct ), ϕ (−∞)=0, ϕ (∞)= κ , of the equation u t ( t ,  x )=Δ u ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 19 publications
0
47
0
Order By: Relevance
“…(1.2) have been considered by many researchers; see, e.g., [2,3,8,9]. For the case where f is non-monotone on [0, K ], i.e., p/δ > e, there are a few results; see [18,10,13,17]. Here, we consider the case for e < p/δ ≤ e 2 .…”
Section: Applicationmentioning
confidence: 97%
“…(1.2) have been considered by many researchers; see, e.g., [2,3,8,9]. For the case where f is non-monotone on [0, K ], i.e., p/δ > e, there are a few results; see [18,10,13,17]. Here, we consider the case for e < p/δ ≤ e 2 .…”
Section: Applicationmentioning
confidence: 97%
“…(1) is separated from zero as x + ct → +∞. The persistence of semi-wavefronts was established in [32] for a local version of model (1). The proof in [32] is based on the local estimations technique which does not apply to Eq.…”
Section: Two Critical Speeds and Non-existence Of Pulse Wavesmentioning
confidence: 98%
“…To my knowledge, no result on uniqueness of critical traveling waves for delayed lattice systems has been reported. Other methods to prove uniqueness of noncritical traveling waves for other types of evolution systems can be found in [1,3,4,5,6,7,11,12]. In [8], it is also shown that for (1.1), the minimal wave speed c * coincides with the spreading speed and the linear determinacy holds for (1.1), meaning that c * is fully determined by the characteristic equation of the linearization of (1.1) at the trivial equilibrium.…”
Section: Introductionmentioning
confidence: 99%